(untitled) (Ciudades, 2018)
Since the end of twentieth century, real estate companies –property developers and builders- have modified their traditional strategies in order to obtain more land to compete in the new territories, diversifying business areas and investing outside. Thanks to it, their monopolistic position has been reinforced even making, with the necessary aid of the institutions, the access to the cities much more difficult and expensive, being those institutions completely unable of stopping the sector extreme voracity.